ความผาสุกทางจิตวิญญาณและความสุขของผู้สูงอายุในศูนย์พัฒนาการจัดสวัสดิการสังคมผู้สูงอายุบ้านบางแค - ชินัณ บุญเรืองรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This is cross-sectional study. It was to study the level of spiritual well-being (SWB), happiness, coordinated factors and compares the correlation outcome between spiritual well-being and happiness in the elderly at Ban Bang Khae Social Welfare Development Center. Elderly were not been sampling. Everyone, who meets the included and excluded criteria, can be selected. 200 Elderly met the study criteria. Five questionnaires were used to identify demographic data, Spiritual Well-Being Scales and Thai happiness indicators (TH-15). Thai Mental Status Exam (TMSE) and Thai Geriatric Depression Scales (TGDS) were used to screen the elderly. All data were counted and analyzed by Chi-square, Regression and Pearson’s Correlation. The results showed that almost of elderly spiritual well being, the prevalence of medium level of SWB and Happiness are 64.5% and 37.5% respectively. Four factors which related significantly to SWB are age; the younger have higher SWB level than the older, underlining disease; elderly, who have underlining disease have higher SWB level than an others, household; elderly who live together have higher SWB level than those who live privacy., and activity participation; elderly who joins activity have higher SWB level. They showed significant at level .01, .05, .05 and .05 respectively. Two factors which related to happiness are age; the older have higher happiness level., and underlining disease; elderly, who have no underlining disease have higher happiness level., significantly. They showed significant at level .01and .05 respectively. Age is the predictor of SWB (.029). This is significant at level .05. Underlining disease is the predictor of happiness (.048). This is significant at level .01. SWB and happiness in this studied showed positive correlated (r = .439) significantly at level .001.